Managing the Livestock Revolution : Policy and Technology to Address the Negative Impacts of a Fast-Growing Sector - World Bank (Washington, DC, 2012)
Fueled by fast-expanding demand, the production of meat and milk in the developing world has doubled in recent decades, and this trend is expected to continue. This expanding sector can provide income, employment, and high quality nutrition for vulnerable groups, and in many areas of the world, essential soil fertility inputs. However, as production grows, market forces, often supported by deliberate or unintended government policies, are causing, in particular in the pig and poultry sector, a spatial concentration of larger-size production units, mostly around urban areas, and an economic concentration of production, processing and retailing. This geographical and economic concentration of the livestock sector probably improves the affordability of meat and milk for the urban poor, and might create better-paid employment up- and downstream of the producer, but has significant negative effects on the environment, animal and human health, and social equity. This paper has the following contents: executive summary; setting the scene - demand patterns, supply patterns, and structural changes; effects of the livestock revolution - environmental, public health, equity, and farm-size interactions; technical solutions, policy and institutional support mechanisms, and current activities, rationale for international involvement, and the way forward.